Financing responsible small- and medium-sized enterprises: An international overview of policies and support programmes - Susanne Durst; Wolfgang Gerstlberger (Journal of Risk and Financial Management, 2021)
In the last few years, the financing of responsibly operating small and medium-sized enterprises (SMEs) has become the focus of attention of several national and international bodies. Consequently, a number of policies and support programmes have been established aimed at supporting SMEs that take a responsible approach concerning the company and its operations. Against this background, this article presents a comprehensive international overview of support programmes for financing responsible SMEs. Based on systematic desk research, documents of national governments as well as supranational and international organisations have been investigated. The findings reveal that there are strong regional differences in terms of support policy approaches, intensity, and criteria. The largest part of the identified programmes has been launched by the European Union and/or its member states. Additionally, the findings clarify that the primary focus of extant programmes is on the environmental dimension of sustainability, mainly energy-related questions. The social dimension has been neglected so far in the programmes.
Keywords: 330; responsible finance; sustainable finance; SMEs; support programmes; grey literature